Texas, our Texas - Banks, James A. (Macmillan/McGraw-Hill, 2003)
The book includes 5 units: Unit 1: Settling the Western hemisphere; Unit 2: From revolution to statehood; Unit 3: Challenge and opportunity; Unit: The 20th century; Unit 5: Texas in the 21st century.